2018
DOI: 10.1108/ijcst-10-2017-0169
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of protective and comfort properties of face masks using superabsorbent polymer containing nanofibers

Abstract: Purpose The purpose of this paper is to introduce a novel face mask prototype having a superabsorbent nanofibrous coating with a homogenous distribution. Design/methodology/approach Superabsorbent nanofibers were manufactured via electrospinning method using Poly(vinyl alcohol)/superabsorbent polymer (PVA/SAP) aqueous polymer solutions and they were simultaneously coated onto face masks in order to develop their virus protection and comfort properties. Absorbency, air permeability, Fourier Transform Infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…2 SEM images of nonwoven composite structures in surgical face mask applications; the approximate scale bar added for better comparison. a) PP spunbond (S) ( Nanjundappa and Bhat, 2005 ), b) PBT meltblown (M) ( Ellison et al, 2007 ), c) PVA electrospun (E) ( Oktay et al, 2014 ), d) PVA/SAP spunbond-electrospun (SE) ( Sivri, 2018 ), e) PCL meltblown-electrospun (ME) ( Erben et al, 2016 ), and f) Hydroentangled spunbond-meltblown-spunbond (SMS) ( Mukhopadhyay, 2014 ), g) Schematic example of commercial face masks structure: surgical face masks and respirators. …”
Section: Filtration Materials and Processmentioning
confidence: 99%
See 2 more Smart Citations
“…2 SEM images of nonwoven composite structures in surgical face mask applications; the approximate scale bar added for better comparison. a) PP spunbond (S) ( Nanjundappa and Bhat, 2005 ), b) PBT meltblown (M) ( Ellison et al, 2007 ), c) PVA electrospun (E) ( Oktay et al, 2014 ), d) PVA/SAP spunbond-electrospun (SE) ( Sivri, 2018 ), e) PCL meltblown-electrospun (ME) ( Erben et al, 2016 ), and f) Hydroentangled spunbond-meltblown-spunbond (SMS) ( Mukhopadhyay, 2014 ), g) Schematic example of commercial face masks structure: surgical face masks and respirators. …”
Section: Filtration Materials and Processmentioning
confidence: 99%
“… Absorb the sweat in the vapor form without transforming into liquid (using superabsorbent polymer). ( Garibaldi et al, 2019 ; He et al, 2020 ; Lee et al, 2020 ; Sivri, 2018 ; Swennen et al, 2020 ; Yang et al, 2017 ) 4 Electrostatic properties Recharging and rejuvenation of used or disinfected surgical face masks, increasing the effective use time of disposable face mask. ( Hossain et al, 2020 ; Wang et al, 2020 ) 5 Special high performance filtering layers Increases the filtration efficiency (nanofiber, hollow fiber, carbon nanotubes, activated carbon, graphene).…”
Section: Multifunctional Surgical Face Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that all face masks were successfully coated with nanofiber, according to Fourier transform infrared spectroscopy (FTIR) investigations and scanning electron microscopy (SEM). Air permeability and capacity to absorb liquids showed that the coating with nanofiber improved the face mask’s hydrophilicity while permeability of air decreased reversely [ 88 ].…”
Section: Electrospun Nanofibers and Their Applications In Face Masks And Respiratorsmentioning
confidence: 99%
“…Obviously the selected active ingredients, which can be used to modify the non-woven fibers and the electrospun polymers, have to be different from those used for the SFMs. The market has been categorized by different companies not only in terms of the economic turnover, size, trends and future challenges of the masks, but also for the raw materials (cotton, polypropylene, paper and others) and the different layers used for their production [12][13][14]. These research studies cover woven and non-woven masks, protective for dust or microorganisms, respectively.…”
Section: Beauty Face Masks (Bfms) Activity and Marketmentioning
confidence: 99%